Serum sodium, cognition and incident dementia in the general population. (2nd February 2023) - van der Burgh, Anna C; Pelouto, Anissa; Mooldijk, Sanne S; Zandbergen, Adrienne A M; Ikram, M Arfan; Chaker, Layal; Hoorn, Ewout J
Abstract: Background: Low serum sodium may be associated with cognitive impairment and dementia in the general population, but the data remain inconclusive. Therefore, we aimed to determine the association of low serum sodium with cognitive function and incident dementia in the general population. Methods: Participants from a prospective population-based cohort were eligible if data on serum sodium (collected between 1997 and 2008), dementia prevalence and dementia incidence were available (follow-up until 2018). Global cognitive function was assessed with the Mini-Mental State Examination (MMSE) and the general cognitive factor (G-factor, derived from principal component analysis of individual tests). Linear regression and Cox proportional-hazards models were used to assess associations of standardised continuous and categorised low serum sodium (mean − 1.96*SD: cut-off of 137 mmol/L) with overall cognitive function and incident dementia, respectively. Results: In all, 8, 028 participants free of dementia at baseline (mean age 63.6 years, 57% female, serum sodium 142 ± 2 mmol/L), including 217 participants with low serum sodium, were included. Cross-sectionally, continuous serum sodium and/or low serum sodium were not associated with the MMSE or G-factor. However, participants with low serum sodium performed worse on the Stroop and Purdue Pegboard tests. During a median follow-up of 10.7 years, 758 subjects developed dementia. Continuous serum sodium (hazard ratio (HR) 0.98, 95% confidence interval (CI) 0.92;1.05) and low serum sodium (HR 1.27, 95% CI 0.90;1.79) were not associated with a higher risk of incident dementia. Conclusion: We identified no significant associations of low serum sodium with overall cognitive functioning and risk of dementia. However, low serum sodium—including levels above the clinical cut-off for hyponatremia—was associated with impairments in selected cognitive domains including attention and psychomotor function.